Penile Degloving Injury in an Adolescent with Congenital Hypothyroid. (25th March 2012) - Kiffin, Chauniqua; Porcelli, Matthew; Prychyna, Oksana; Pazmino, Byron; Pust, Daniel; DeCostanza, Joseph
Abstract : This case follows a 17-year-old boy with congenital hypothyroidism who sustained penile skin avulsion secondary to a dog bite. Initially, an attempt was made to repair the wound using the avulsed skin flap itself as coverage. The repair was done immediately upon presentation to enhance the chances of adequate flap viability; however, the dorsal portion of the reconstruction necrosed within the following week. Ultimately a full thickness surgical graft (FTSG) repair was performed to ensure the most desirable outcome.